Making connections: Elementary students' ideas about electricity and energy resources. (August 2019) - Merritt, Eileen G.; Bowers, Nicole; Rimm-Kaufman, Sara E.
Abstract: The development of energy literacy for all citizens is critical as we face climate change and rapid depletion of existing energy resources. This study explores energy literacy development in fourth grade classrooms. Our team developed a curriculum on energy resources aligned with the Next Generation Science Standards. We then trained teachers how to implement the program and support their students' engagement in a service-learning project related to energy conservation. We used qualitative methods to analyze students' open-ended responses from an energy literacy assessment. Students were familiar with solar, hydropower and wind energy, and suggested that solar energy should be used more in the future. Students were more easily able to explain energy transfer in wind turbines and solar panels than in other electricity production systems. Students learned important energy and natural resource concepts in the context of an environmental service-learning program. Discussion focuses on the importance of integrated science instruction that helps students see how their electricity use impacts the environment, and provides them with opportunities to take action. We also suggest important ways that renewable energy companies can contribute to energy and climate literacy initiatives. Highlights: Fourth grade students can understand the connections between the electricity use and natural resources. Modeling energy systems can help children make sense of energy transfer and evidence of energy. Wind turbines and solar panels are a good entry point for energy literacy initiatives in younger grades. Service-learning programs can foster energy and climate literacy development through exploration of energy problems and solutions.